2022
DOI: 10.3389/fmed.2022.914424
|View full text |Cite
|
Sign up to set email alerts
|

Stopping of Mycophenolic Acid in Kidney Transplant Recipients for 2 Weeks Peri-Vaccination Does Not Increase Response to SARS-CoV-2 Vaccination—A Non-randomized, Controlled Pilot Study

Abstract: IntroductionKidney transplant recipients (KTR) are at high risk of developing severe COVID-19. However, vaccine response in this population is severely impaired with humoral response rates of 36–54 and 55–69% after two or three doses of SARS-COV-2 vaccines, respectively. Triple immunosuppression and specifically the use of anti-proliferative agents such as mycophenolic acid (MPA) or azathioprine (AZA) have been identified as risk factors for vaccine hypo-responsiveness.MethodsWe hypothesized that in vaccine no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 20 publications
3
26
0
Order By: Relevance
“…The latter observation is consistent with the data obtained in adolescent [4,7] and adult [20][21][22][23][24][25][26][27] KTR. It is currently being investigated in adults whether the transient halt of MMF therapy increases the rate of vaccine responders without an undue risk of kidney allograft rejection [28,29]. However, severe COVID-19 in pediatric patients on immunosuppressive therapy is rare [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…The latter observation is consistent with the data obtained in adolescent [4,7] and adult [20][21][22][23][24][25][26][27] KTR. It is currently being investigated in adults whether the transient halt of MMF therapy increases the rate of vaccine responders without an undue risk of kidney allograft rejection [28,29]. However, severe COVID-19 in pediatric patients on immunosuppressive therapy is rare [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…While belatacept treatment and MPA dose have been reported as negative predictors of serological vaccine response throughout the literature ( 10 ), it is still unclear, whether modulation of immunosuppression, and especially pausing MPA can increase serological response to SARS-CoV-2 vaccination, since most data originate from observational or small non-randomized controlled trials ( 5 , 31 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of MPA dose pause for one week before and four weeks after vaccination also revealed improvement in serologic response [ 16 ]. In another study with a shorter period, two weeks of immunosuppressive drug modification revealed an inadequate immune response [ 31 ]. Since the immune system requires a certain amount of time to respond after suppression or cessation of immunosuppression [ 32 ], thus, a two-week duration of immunosuppressive regimen switching prior to vaccination will allow the immune system to be restored, and another two weeks after vaccination can help the body to build an immune response to vaccination.…”
Section: Discussionmentioning
confidence: 99%